Development and psychometric testing of an instrument for team-based learning assessment - Rita Mojtahedzadeh; Aeen Mohammadi; Sima Kolahdooz; Dean X. Parmelee; Gholamreza Hassanzadeh (Journal of Education and Health Promotion, 2024)
BACKGROUND: In team-based learning (TBL), students actively participate in the learning process and are responsible for their learning through preclass studying and team work with other classmates. Evaluation of the TBL method by students provides information for its better implementation. Due to extensive use of TBL method in medical curriculum at medical universities, we aimed to develop a questionnaire for its evaluation from the viewpoints of students. MATERIALS AND METHODS: This mixed-method cross-sectional study with a Qual-Quan design was conducted on 168 medical students in the basic sciences stage of their studies. We evaluated students’ satisfaction with this teaching method and its effectiveness by semistructural in-depth individual interviews until data saturation (12 interviews). We performed content analysis of the interviews and designed the questionnaire. Psychometric characteristics of the questionnaire were assessed in terms of content validity, test-retest reliability, internal consistency, and construct validity through explanatory factor analysis. RESULTS: The final tool was a 25-item questionnaire (reliability = 0.87 and α = 0.93) with five components of “learning enhancement,” “satisfaction,” “technical aspects,” “teacher’s capabilities,” and “appropriate testing.” Explanatory factor analysis showed that 64.68% of total variances were explained by these five components. CONCLUSION: In addition to academic performance outcomes, a successful instructional strategy should generate positive experiences for the learner. This study has created an assessment tool to be part of an evaluation process of the effectiveness of TBL in a given curriculum for medical students.